Photo-induced stress relaxation in reconfigurable disulfide-crosslinked supramolecular films visualized by dynamic wrinkling - Yan, Shuzhen; Hu, Kaiming; Chen, Shuai; Li, Tiantian; Zhang, Wenming; Yin, Jie; Jiang, Xuesong (Nature communications, 2022)
Stress relaxation in reconfigurable supramolecular polymer networks is strongly related to intermolecular behavior. However, the relationship between molecular motion and macroscopic mechanics is usually vague, and the visualization of internal stress reflecting precise regulation of molecules remains challenging. Here, we present a strategy for visualizing photo-driven stress relaxation induced by infinitesimal perturbations in the intermolecular exchange reaction via reprogrammable wrinkle patterns. The supramolecular films exhibit visible changes in microscopic wrinkle topography through ultraviolet (UV)-induced dynamic disulfide exchange reaction. In accordance with the trans-scale theoretical models, which quantitatively evaluate the chemical-dependent mechanical stresses in the supramolecular network, the unexposed disordered wrinkles evolved into highly oriented patterns and underwent subsequent mutations after thermal treatment. The stress-sensitive wrinkle macro-patterns can be repetitively written/erased through network topology rearrangement using different stimuli. This strategy provides an approach for visualizing and understanding the molecular behavior from dynamic chemistry to mechanical changes, and directly programming wrinkle patterns with regulated structures. The mechanics of reconfigurable supramolecular polymer networks are governed by their dynamic crosslinking chemistry and the resulting stress relaxations. Here, the authors use reversible wrinkling patterns to visualize localized stress relaxations, due to molecular network rearrangements.